Muscle dysmorphia symptomatology and related factors - Sanchez-Castro, Ana Elena (2019)
Muscle dysmorphia is an obsessive-compulsive disorder subcategorized as a body dysmorphic disorder. Studies in Latin America have assessed the prevalence of muscle dysmorphia in bodybuilders and gym users. Therefore, the purpose of this study was to evaluate the prevalence of muscle dysmorphia symptomatology (MDS) and associated factors in university male students in Lima, Peru. The participants (N = 618) had an average age of 21.0 years (DS = 2.3). We assessed MDS through the Muscular Appearance Satisfaction Scale (MASS) and obsessive-compulsive disorders through the Yale-Brown Scale Modified for Body Dysmorphic Disorders (BDD-YBOCS). We also tested participants on their food consumption and physical activity (PA) frequency. The prevalence of MDS was 1.3% (IC 95% = 0.4-2.2%) . associated with factors such as intense PA defined as more than five hours per week (PRa = 9.5; 95% CI = 1.1-84.4) and a hyperproteic diet (PRa = 1.3; 95% CI = 1.1-1.6). Thirty-two percent of participants consumed protein supplements. Muscle dysmorphia is a disorder present in the general population. However, more research must be done to understand how this is an emerging problem in Latin America. Therefore, to influence its prevention and early identification among the university population, it is necessary to deepen the understanding.